Manifestations of vulnerability in narcissistic personality disorder: a review - Daniel Pledger; Mark Hardaker; Elias Tsakanikos (Academia Mental Health & Well-Being)
Background: Despite evidence of at least two dimensions of narcissism, termed grandiose and vulnerable, vulnerability within narcissistic personality disorder (NPD) is still often underacknowledged. This narrative review aimed to identify which vulnerabilities are present within NPD patients, and how such vulnerabilities manifest. Methods: A comprehensive search was conducted in PubMed, EMBASE, PsycINFO and Web of Science databases. Only studies including participants with a diagnosis of NPD according to the DSM were included. A total of 2500 results were screened and 37 were included in this review. Results: NPD patients frequently present with a range of different vulnerabilities. We found consistent associations between NPD and depression, hypersensitivity, distrust and shame. Limited existing literature supported an association between NPD and insecure attachment, anxiety, insecure identity and perfectionism. The links between NPD, low self-esteem and psychological distress were inconsistent. Almost half of the included studies were case studies of single patients, and many participants had significant psychiatric comorbidities, which may limit the generalizability of our findings. Conclusions: Narcissistic vulnerabilities are frequent within NPD and can hinder a patient’s treatment adherence and engagement. These vulnerabilities may make suitable targets for therapeutic interventions. Increasing clinicians’ awareness of narcissistic vulnerabilities may help them navigate the associated interpersonal dysfunction.